SOCIAL MECHANISMS OF COMMUNITY INFLUENCE ON THE DEVELOPMENT OF LEADERSHIP QUALITIES OF ADOLESCENTS (World Bulletin of Social Sciences, 2024)
This article provides information on some trends in modern society that allow a new way of looking at long-term problems, showing initiative, mobility, competition - the most important human qualities, as well as some trends in teaching the formation of social mechanisms of social impact of likeminded people.